Reactive agility—evidence based suggestions for improvement - Vogt, L.; Laukhardt, F.; Haser, C.; Banzer, W.; Engeroff, T. (Frontiers in Sports and Active Living, 2026)
Purpose: To examine the contributions of lower-limb eccentric strength, reactive strength, and cognitive inhibitory control to reactive agility performance.